2019
DOI: 10.3389/fgene.2019.00962
|View full text |Cite
|
Sign up to set email alerts
|

Essential Role of Histone Replacement and Modifications in Male Fertility

Abstract: Spermiogenesis is a complex cellular differentiation process that the germ cells undergo a distinct morphological change, and the protamines replace the core histones to facilitate chromatin compaction in the sperm head. Recent studies show the essential roles of epigenetic events during the histone-to-protamine transition. Defects in either the replacement or the modification of histones might cause male infertility with azoospermia, oligospermia or teratozoospermia. Here, we summarize recent advances in our … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
82
0
4

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 105 publications
(91 citation statements)
references
References 147 publications
1
82
0
4
Order By: Relevance
“…Histones are widely replaced from the sperm genome and depending of the analyzed specie, the rate of retention varies. As we will describe below, it seems that histone replacement in the sperm genome has become a more understood mechanism (broadly reviewed in Bao and Bedford, 2016;Wang et al, 2019), whereas a nucleosome retention mechanism is still at large.…”
Section: Histone Replacement In the Sperm Genomementioning
confidence: 99%
“…Histones are widely replaced from the sperm genome and depending of the analyzed specie, the rate of retention varies. As we will describe below, it seems that histone replacement in the sperm genome has become a more understood mechanism (broadly reviewed in Bao and Bedford, 2016;Wang et al, 2019), whereas a nucleosome retention mechanism is still at large.…”
Section: Histone Replacement In the Sperm Genomementioning
confidence: 99%
“…As mentioned in previous literature, a nucleotide variation by demolishing or generating a connection in the regulatory gene network may activate or inhibit the expression of target genes (Wang & Batmanov, 2015). Additionally, the cDNA.42G>A variation was detected as a promoter-associated region and generally had regulatory features such as H3K27ac and H3K36me3, which it has been authenticated that H3 contributes to the PRM1 incorporation (Kouzmenko et al, 2019). Also, Tong et al, handled a study on mice cell line and through enriching spermatocytes and round spermatids, indicated H3K36me3 regulate the TNPs and PRMs genes expression (Tong, 2018).…”
Section: Ta B L Ementioning
confidence: 65%
“…In particular, an unusually high abundance of histone variants has been identified as an epigenetic error contributing to failed embryo development [ 134 ]. Beyond histone variants, the complex picture of histone modifications has also been described as an important quality marker of sperm, as recently reviewed [ 74 , 135 ].…”
Section: Epigenetic Signature Of Male Germlinementioning
confidence: 99%